24th International Conference on Offshore Mechanics and Arctic Engineering: Volume 3 2005
DOI: 10.1115/omae2005-67055
|View full text |Cite
|
Sign up to set email alerts
|

Change of Mechanical Properties of High Strength Line Pipe by Thermal Coating Treatment

Abstract: In strain-based design, the overmatch condition in the girth weld portion primarily must be maintained. The pipes may also be required to have a low yield to tensile (Y/T) ratio and a high uniform elongation (U.EL) in the longitudinal direction to achieve a high compressive buckling strain. However, change in the mechanical properties by heating during coating treatment has not been paid attention so much. Furthermore, how much the mechanical properties change is affected by production conditions is unclear. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Unfortunately, the steel pipes reveal discontinuous yielding behavior after anti-corrosion coating process, so-called occurrence of strain aging. Then deformability of the linepipes significantly degraded [4][5][6]. Thus, we investigated the exact mechanism of strain aging in linepipe steels and based on it we tried to fabricate SBD X80 and X100 linepipe steels.…”
Section: Linepipe Steels For Strain-based Designmentioning
confidence: 99%
“…Unfortunately, the steel pipes reveal discontinuous yielding behavior after anti-corrosion coating process, so-called occurrence of strain aging. Then deformability of the linepipes significantly degraded [4][5][6]. Thus, we investigated the exact mechanism of strain aging in linepipe steels and based on it we tried to fabricate SBD X80 and X100 linepipe steels.…”
Section: Linepipe Steels For Strain-based Designmentioning
confidence: 99%
“…[1][2][3] Pipeline steels are used after the piping and corrosion-resistant coating processes, in which uniform elongation and the deformability decrease because of the strain aging phenomenon. [4][5][6] To restrain the strain aging phenomenon during the piping and corrosion-resistant coating processes, many studies have been conducted to reduce the number of carbon atoms in ferrite and to form more cementite. [7][8][9] Shigesato et al [7] reported that cementites were distributed uniformly when Cr was added in American Petroleum Institute (API) X80 pipeline steels.…”
mentioning
confidence: 99%
“…[4][5][6] To restrain the strain aging phenomenon during the piping and corrosion-resistant coating processes, many studies have been conducted to reduce the number of carbon atoms in ferrite and to form more cementite. [7][8][9] Shigesato et al [7] reported that cementites were distributed uniformly when Cr was added in American Petroleum Institute (API) X80 pipeline steels. When Mo was added to the API X80 pipeline steels, however, the cementites were not distributed uniformly but were almost formed in the narrow space of the bainite lath; hence, the uniform elongation and deformability of the API X80 pipeline steels decreased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In the Cottrell atmosphere, the decrease in uniform elongation is caused by the interactions between the carbon atoms in ferrite and dislocations, which results in yield point phenomena during the tensile tests. [5,6] Many studies have been conducted to form large amounts of cementite in linepipe steels and to reduce the number of carbon atoms in ferrite because carbon atoms are the main factors for the strain aging phenomena. [7][8][9][10][11][12] The finish cooling temperatures strongly affect the formation of secondary phases, such as cementite and martensite-austenite constituents (MA).…”
Section: Introductionmentioning
confidence: 99%